X-ray diffuse scattering observations for SrxBa1−xNb2O6 single crystals with x=0.35 and 0.81. (3rd October 2018) - Paściak, M.; Kopecký, M.; Kub, J.; Fábry, J.; Dec, J.; Ondrejkovic, P.; Hlinka, J.; Buixaderas, E.
ABSTRACT: In an attempt to contribute to understanding of structure–property relationship in ferroelectric relaxor Sr x Ba 1 − x Nb 2 O 6, we studied X-ray diffuse scattering for compositions with x = 0.35 and x = 0.81 at room temperature. Within signal-rich reciprocal-space images, features related to (i) local deformation due to chemical inhomogeneity, (ii) incommensurate modulation and (iii) fluctuation of polarization have been identified. There are substantial differences between the two compositions, some of which can be straightforwardly attributed to different states of ferroelectric ordering in these materials. In the Sr-rich composition, we have observed additional features in the form of ⟨ 110 ⟩ -oriented streaks on h k ( n / 2 ) planes. They indicate that transverse correlation of uniaxial polarization is anisotropic. At the same time, the fact that streaks appear also on the superlattice planes raises the question whether the modulation and polarization order parameter are interrelated.